2015
DOI: 10.2209/tdcpublication.56.259
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Cation Channel Subfamily Vanilloid Member 3 is not Involved in Plasma Membrane Stretch-induced Intracellular Calcium Signaling in Merkel Cells

Abstract: Merkel cells (MCs), which form part of the MC-neurite complex, making contact with sensory afferents to drive mechanosensory transduction mechanisms, express transient receptor potential (TRP) cation channel subfamily vanilloid (V) members 1, 2, and 4, as well as ankyrin subfamily member 1. While these proteins are involved in sensing plasma membrane stretch, less is known about the functional properties of TRPV subfamily member 3 (TRPV3) during membrane stretch in MCs. The aim of this study was to determine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Synthetic and natural compounds, like isopentenyl pyrophosphate (Bang et al, 2011), 17(R)-resolvin D1 (Bang et al, 2012), forsythoside B (Zhang et al, 2019), diphenyltetrahydrofuran osthole (Higashikawa et al, 2015) and ruthenium red (Xu et al, 2002) have been proposed to inhibit TRPV3 channels. Due to either or both the lack of targeting specificity and the clinical application, their remedial potential remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic and natural compounds, like isopentenyl pyrophosphate (Bang et al, 2011), 17(R)-resolvin D1 (Bang et al, 2012), forsythoside B (Zhang et al, 2019), diphenyltetrahydrofuran osthole (Higashikawa et al, 2015) and ruthenium red (Xu et al, 2002) have been proposed to inhibit TRPV3 channels. Due to either or both the lack of targeting specificity and the clinical application, their remedial potential remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…for the role of TRPV3 or TRPV5 in the mechanotransduction. Additionally, in the study by Higashikawa et al, TRPV3 was not found to be stimulated by mechanical stretching [202]. It has, however, been shown that TRPV3 forms a signaling complex with TGF-α and EGFR and that this complex plays a role in the mechanical skin barrier function [203].…”
Section: Are All the Trpv Channels Mechanosensitive?mentioning
confidence: 98%